p-Methoxycinnamic Acid Diesters Lower Dyslipidemia, Liver Oxidative Stress and Toxicity in High-Fat Diet Fed Mice and Human Peripheral Blood Lymphocytes - Paim, Raquel Teixeira Terceiro (Nutrients, 2020)
The pursuit of cholesterol lowering natural products with less side effects is needed for controlling dyslipidemia and reducing the increasing toll of cardiovascular diseases that are associated with morbidity and mortality worldwide. The present study aimed at the examining effects of p-methoxycinnamic acid diesters (PCO-C) from carnauba (Copernicia prunifera)-derived wax on cytotoxic, genotoxic responses in vitro and on dyslipidemia and liver oxidative stress in vivo, utilizing high-fat diet (HFD) chronically fed Swiss mice. In addition, we evaluated the effect of PCO-C on the expression of key cholesterol metabolism-related genes, as well as the structural interactions between PCO-C and lecithin-cholesterol acyl transferase (LCAT) in silico. Oral treatment with PCO-C was able to reduce total serum cholesterol and low-density lipoprotein (LDL) levels following HFD. In addition, PCO-C reduced excessive weight gain and lipid peroxidation, and increased the gene expression of LCAT following HFD. Furthermore, the high affinity of the studied compound (ΔG: −8.78 Kcal/mol) towards the active sites of mutant LCAT owing to hydrophobic and van der Waals interactions was confirmed using bioinformatics. PCO-C showed no evidence of renal and hepatic toxicity, unlike simvastatin, that elevated aspartate aminotransferase (AST) levels, a marker of liver dysfunction. Finally, PCO-C showed no cytotoxicity or genotoxicity towards human peripheral blood lymphocytes in vitro. Our results suggest that PCO-C exerts hypocholesterolemic effects. The safety of PCO-C in the toxicological tests performed and the reports of its beneficial biological effects render this a promising compound for the development of new cholesterol-lowering therapeutics to control dyslipidemia. More work is needed for further elucidating PCO-C role on lipid metabolism to support future clinical studies.